UNIQUE PRINCIPLES OF COMPLEMENT BINDING REACTION - Umarova Tamila Abdufattoevna; Kudratova Zebo Erkinovna; Xodjimetova Ruxshona; Raxmatova Madina (Web of Journals Publishing, 2024)
The unique ability of complement to bind specifically to antigen-antibody complexes of different nature has been utilised in the complement binding reaction (CBR) proposed in 1901 by J. Borde and O. Jangou. The particular advantage of the complement binding reaction is that the nature of the antigen involved (corpuscular or soluble) is irrelevant, since complement binds to the Fc-fragment of any IgG and IgM antibody, irrespective of its antigenic specificity.
Keywords: antibodies, antigens, specificity, immune complex, complement system;